Daily Low-Dose Cisplatin-Based Concurrent Chemoradiotherapy in Patients With Uterine Cervical Cancer With Emphasis on Elderly Patients: A Phase 2 Trial. Issue 8 (1st October 2013) - Mitsuhashi, Akira; Uno, Takashi; Usui, Hirokazu; Nishikimi, Kyoko; Yamamoto, Noriko; Watanabe, Miho; Tate, Shinichi; Hirashiki, Koichiro; Kato, Kazuyoshi; Yamazawa, Koji; Shozu, Makio
Abstract : Objective: We evaluated the usefulness of daily low-dose cisplatin-based concurrent chemoradiotherapy (daily CCRT) in patients with cervical cancer with an emphasis on elderly patients. Methods: Between January 2003 and December 2008, a total of 65 patients with untreated stage IIA to IIIB cervical cancer were enrolled and 54 were selected for this nonrandomized prospective study. The daily CCRT comprised pelvic external beam radiotherapy (2 Gy/d × 25) with daily low-dose cisplatin (8.0 mg/m 2 per day) and either low- or high-dose rate intracavitary brachytherapy. Results: The median age of the patients was 62 years (range, 29–85 years), and 21 patients (39%) were 70 years or older. The median follow-up period was 47 months (range, 4–107 months). Daily CCRT was successfully completed in 91% (49/54) of the patients. The mean total cisplatin dose was 191 mg/m 2 (range, 128–224 mg/m 2 ), and a neutropenia grade higher than 3 was observed in 24% of the patients. Of the 21 patients 70 years or older, 17 (81%) completed daily CCRT with acceptable toxicity. The 3-year overall survival (OS) rate for all the patients was 82.9%. No statistically significant differences in the OS rate and toxicity were observed between patients 70 years or older and those younger than 70 years. Conclusions: Daily CCRT showed acceptable toxicity and compliance, leading to the use of a high total dosage of cisplatin. The OS rate for daily CCRT was comparable to that for previously reported weekly CCRT. Daily CCRT could be an alternate choice for the CCRT treatment in elderly patients with cervical cancer.